An examination of psychological issues in the pregnancy and birth process with reference to personal responsibility and control - Selwyn-Cross, Halina (Rhodes University, Faculty of Humanities, Department of Psychology, 1991)
This study examines the psychological issues of personal responsibility and control in the childbirth process. It examines the implications of the woman's preparation process and the choices she makes during pregnancy and childbirth. It also explores the way in which the birthing environment and the woman's interpersonal relationships affect her experience of personal control within the context of the childbirth period. Use was made of the case study research design. This qualitative design involved indepth exploration, of cases in which the women had recently given birth to their first child in the local hospital of a small town. The data analysis involved the use of a "reading guide", established by the researcher to allow for the examination of the data specifically in terms of the themes in question. Within the study the importance and value of the woman's accurate and sufficient preparation for the birth was seen to facilitate a realistic sense of predictability, which led to an increased awareness and ability of the woman to remain in control. This, along with the active participation of the husband and supportive network in the hospital, allowed for a sharing of the responsibility within the labour situation. This taking and appropriately yielding of control and responsibility had positive effects on the woman's experience of the event and for initial mother-infant bonding
Keywords: Childbirth -- Psychological aspects; Pregnancy -- Psychological aspects